Electrolyte, battery and electric equipment

By adding sulfide ether and cyclic sulfonate additives to the electrolyte of lithium-ion energy storage batteries, the problem of instability of the electrolyte at high temperatures is solved, and the high temperature stability and safety performance of the battery are improved.

CN119674224APending Publication Date: 2025-03-21XIAMEN HITHIUM ENERGY STORAGE TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411918148.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Lithium-ion energy storage batteries have the problem of electrolyte instability in high temperature environments, which affects the performance and life of the battery cell and may cause safety hazards.

Method used

An electrolyte containing sulfide-ether additives and cyclic sulfonate additives is used. The sulfide-ether additive reduces the transmission impedance of lithium ions by forming a polysulfide-ether derivative, and the cyclic sulfonate additive improves the thermal stability of the electrolyte by forming a SEI film.

Benefits of technology

It improves the thermal stability and ionic conductivity of the electrolyte, extends the cycle life of the battery, and improves the safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674224A_ABST
    Figure CN119674224A_ABST
Patent Text Reader

Abstract

The invention relates to an electrolyte, a battery and electric equipment. The electrolyte comprises a first additive and a second additive, the first additive is a thioether additive, and the end group of the first additive comprises a reactive group; and the second additive is a cyclic sulfonate additive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to an electrolyte, a battery and an electrical device. Background Art

[0002] With the development of the energy storage industry, lithium-ion battery technology has continued to develop and is widely used in electric vehicles, mobile devices, energy storage systems and other fields. However, other user scenarios on the wind and solar power generation side require lithium-ion energy storage batteries to have a lower life attenuation amplitude and a longer service life. At the same time, lithium-ion cells have the problem of electrolyte instability in high temperature environments, which will not only affect the performance and life of the cells, but may also cause safety hazards. However, with the increasing energy density and increasing cell integration of current large-scale energy storage batteries, the challenge of maintaining safety is becoming increasingly greater. Therefore, there is an urgent need for an electrolyte with good thermal stability to improve the safety performance of lithium-ion energy storage batteries. Summary of the invention

[0003] In view of this, the present application provides an electrolyte, a battery and an electrical device, wherein the electrolyte has good thermal stability.

[0004] The present application provides an electrolyte, which includes: a first additive and a second additive, wherein the first additive is a thioether additive, and the end group of the first additive includes a reactive group; and the second additive is a cyclic sulfonate additive.

[0005] Furthermore, the structural formula of the first additive is: Among them, R1 is selected from at least one of vinyl, ethynyl and propylene oxide; R2 is selected from at least one of vinyl, ethynyl and propylene oxide.

[0006] Furthermore, the first additive is selected from and At least one of .

[0007] Furthermore, in the electrolyte, the mass fraction a of the first additive is in the range of 0.1%≤a≤2%.

[0008] Furthermore, the structural formula of the second additive is: Wherein, R3 is selected from at least one of methyl, ethyl, propyl, butyl and sulfonate groups.

[0009] Furthermore, the second additive is selected from and At least one of .

[0010] Furthermore, in the electrolyte, the mass fraction b of the second additive is in the range of 0.1%≤b≤3%.

[0011] Furthermore, in the electrolyte, the mass fraction of the first additive is a, and the mass fraction of the second additive is b, then the relationship is satisfied: 0.1≤a / b≤2.

[0012] The present application provides a battery, which includes: an electrode assembly and an electrolyte provided in the present application, wherein the electrode assembly includes a positive electrode plate, a separator and a negative electrode plate; the electrolyte is used to infiltrate at least a portion of the electrode assembly.

[0013] The present application provides an electrical device, which includes: a device body and a battery provided in the present application, wherein the battery supplies power to the device body.

[0014] In the present application, the electrolyte includes a first additive, the first additive is a thioether additive and the end group is a reactive group. In other words, the first additive includes a thioether bond, and the multiple reactive groups react with each other to generate a polythioether derivative with a higher degree of polymerization. The sulfur in the polythioether derivative contains lone pairs of electrons, which are easier to coordinate and deintercalate with lithium ions, so that the polythioether derivative has a stronger interaction with lithium ions, which is beneficial to reduce the impedance of lithium ion transmission in the electrolyte. Furthermore, the polythioether derivative has a low solubility in the electrolyte and can be preferentially adsorbed on the damaged surface of the negative electrode plate to further reduce the interface impedance of lithium ions entering from the electrolyte to the negative electrode plate, reduce the charge transfer impedance, and promote the desolvation process of lithium ions at the interface between the electrolyte and the negative electrode plate. Further, the protective film formed by the polythioether derivative on the surface of the negative electrode plate has good flexibility, which is beneficial to accelerate the transmission speed of lithium ions and ultimately improve the cycle capacity retention rate of the battery. In addition, the electrolyte also includes a second additive, which is a cyclic sulfonate additive. The second additive breaks the SO bond in the electrolyte, opens the ring and forms a flexible SEI (Solid Electrolyte Interface) film containing polysulfonate at the interface between the negative electrode and the electrolyte. The SEI film has good chemical stability, thereby improving the stability of the electrolyte at high temperatures. The polysulfonate formed by the second additive will further decompose into inorganic components such as lithium sulfonate and lithium sulfide, so that the inorganic components in the SEI film increase, further improving the thermal stability of the SEI film. When the electrolyte includes both the first additive and the second additive, the first additive and the second additive have a synergistic effect. On the first aspect, the polysulfide derivative generated by the first additive is adsorbed on the surface of the negative electrode plate, and the polysulfide derivative has a strong interaction with lithium ions, which is beneficial to increase the concentration of lithium ions at the interface between the negative electrode plate and the electrolyte. The greater the concentration of lithium ions, the higher the concentration of reactants in the decomposition reaction of the polysulfonate generated by the second additive, which is beneficial to promote the right shift of the decomposition reaction equilibrium of the polysulfonate, promote the decomposition of the polysulfonate and form lithium sulfonate, lithium sulfide, etc. The SEI film includes organic substances such as polysulfide derivatives and polysulfonates, and includes inorganic substances such as lithium sulfide and lithium sulfonate. Polysulfide derivatives, polysulfonates, lithium sulfide, and lithium sulfonate all contain sulfur, and there is an intermolecular synergistic effect. The stability of the SEI film at high temperature is improved without reducing the conductivity of the SEI film, so that the electrolyte has good stability at both room temperature and high temperature.On the second aspect, the SEI film containing polysulfonate formed by the second additive has a low ionic conductivity at the interface of the negative electrode plate, which may cause the battery to have a rapid increase in initial impedance when the electrolyte is applied to the battery, thereby reducing the room temperature performance of the battery. Correspondingly, the polysulfide derivative formed by the first additive has excellent ion conductivity, and the first additive can neutralize the deficiencies of the second additive in ion conductivity, so that the electrolyte also has good ion conductivity at room temperature. On the third aspect, the first additive can make the final SEI film have an inorganic component of lithium sulfide, which is beneficial to improve the thermal stability of the SEI film, thereby improving the thermal stability of the electrolyte. In summary, the electrolyte of the present application has good thermal stability and high ionic conductivity. When the electrolyte is applied to a battery, the battery has good cycle performance and high safety performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the implementation will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0016] Figure 1 A partial cross-sectional structural schematic diagram of a battery according to an embodiment of the present application;

[0017] Figure 2 This is a schematic diagram of the structure of an electrical device according to an embodiment of the present application;

[0018] Figure 3 This is a circuit block diagram of an electrical device according to an embodiment of the present application.

[0019] Description of reference numerals:

[0020] 100 - electrolyte, 200 - battery, 210 - electrode assembly, 211 - positive electrode plate, 212 - diaphragm, 213 - negative electrode plate, 300 - electrical equipment, 310 - equipment body. DETAILED DESCRIPTION

[0021] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0022] The terms "first", "second", etc. in the specification and claims of this application and the above-mentioned drawings are used to distinguish different objects, rather than to describe a specific order. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not limited to the listed steps or units, but optionally includes steps or units that are not listed, or optionally includes other steps or units inherent to these processes, methods, products or devices.

[0023] Reference to "embodiment" or "implementation" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiment or implementation may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0024] With the development of the energy storage industry, lithium-ion battery technology has continued to develop and is widely used in electric vehicles, mobile devices, energy storage systems and other fields. However, other user scenarios on the wind and solar power generation side require lithium-ion energy storage batteries to have a lower life attenuation amplitude and a longer service life. At the same time, lithium-ion cells have the problem of electrolyte instability in high temperature environments, which will not only affect the performance and life of the cells, but may also cause safety hazards. However, with the increasing energy density and increasing cell integration of current large-scale energy storage batteries, the challenge of maintaining safety is becoming increasingly greater. Therefore, there is an urgent need for an electrolyte with high thermal stability to improve the safety performance of lithium-ion energy storage batteries.

[0025] At present, most companies in the energy storage field use lithium iron phosphate as the main positive electrode active material. Lithium iron phosphate has the advantages of not easy to release oxygen, good electrochemical and thermal stability, but it also has the defect of low energy density. In order to improve the energy density of lithium iron phosphate energy storage cells and reduce the production cost, higher electrode coating and higher cold pressing density are used. At the same time, the capacity of single cells is getting larger and larger. On the basis of the same active material capacity, the amount of current collector and electrolyte used is reduced. While these strategies bring high energy density and reduce costs, the stability of cells under high temperature conditions is becoming increasingly prominent. In large-capacity cells, the cells generate high heat and have poor heat dissipation. During operation, heat accumulates, and the electrolyte is easy to decompose and evaporate, resulting in increased pressure inside the cell, and may even cause the cell to catch fire and explode. Therefore, by selecting solvents and additives with high thermal stability, conductivity and safety, the performance and life of lithium-ion cells in high temperature environments can be improved.

[0026] It can be understood that a higher electrode coating means that the positive electrode active material in the electrode has a higher coating amount, and a higher cold pressing density means that the positive electrode has a higher compaction density.

[0027] See also Figure 1 The present application provides a battery 200, which includes: an electrode assembly 210 and an electrolyte 100 provided in the present application, wherein the electrode assembly 210 includes a positive electrode plate 211, a separator 212 and a negative electrode plate 213; the electrolyte 100 is used to infiltrate at least a portion of the electrode assembly 210.

[0028] It can be understood that in the electrode assembly 210 , the positive electrode plate 211 , the separator 212 , and the negative electrode plate 213 are stacked.

[0029] Optionally, in some embodiments, the battery 200 is a lithium-ion battery.

[0030] It can be understood that the electrolyte 100 is used to infiltrate the electrode assembly 210 to achieve the transmission of active ions in the battery 200 between the positive electrode plate 211 and the negative electrode plate 213. When the battery 200 is a lithium-ion battery 200, the active ions are lithium ions.

[0031] In this embodiment, the battery 200 includes the electrolyte 100 provided in the embodiment of the present application, and the electrolyte 100 includes a first additive and a second additive, and the first additive is a thioether additive, and the end group of the first additive includes a reactive group; the second additive is a cyclic sulfonate additive. The first additive and the second additive have a synergistic effect. The polysulfide derivative generated by the first additive is adsorbed on the surface of the negative electrode plate 213, and the polysulfide derivative has a strong interaction with lithium ions, which is beneficial to increase the concentration of lithium ions on the interface between the negative electrode plate 213 and the electrolyte 100, thereby promoting the second additive to form polysulfonate and decompose into inorganic substances such as lithium sulfonate and lithium sulfide, so as to increase the inorganic component of the SEI film on the surface of the negative electrode plate 213 and improve the thermal stability of the SEI film. The electrolyte 100 has not only good ion transmission performance at room temperature and high temperature environment, but also good thermal stability, so that the battery 200 has good cycle performance and good safety performance at both room temperature and high temperature environment. At the same time, the battery 200 has good high temperature storage performance, so the battery 200 can be stored and used in a high temperature environment, so as to expand the applicable scenarios of the battery 200 and improve the performance of the battery 200.

[0032] It can be understood that in the terminology of this application, "high temperature" is relative to "normal temperature", normal temperature generally refers to room temperature, such as between 10° C. and 30° C., and high temperature generally refers to more than 30° C. This is only an example of high temperature and normal temperature, and should not be understood as a limitation on high temperature and normal temperature.

[0033] It can be understood that, in the terminology of the present application, “high temperature storage performance” can represent the stability of the battery 200 when stored in a high temperature environment.

[0034] Understandably, Figure 1 The battery 200 shown is a cylindrical battery, and the battery 200 may also be a square battery. Figure 1 The embodiment merely provides an illustration of the battery 200 and should not be construed as limiting the shape of the battery 200 .

[0035] Optionally, in some embodiments, the diaphragm 212 is a polypropylene diaphragm, a polyethylene diaphragm or a coated diaphragm.

[0036] Optionally, the positive electrode plate 211 includes a stacked positive electrode collector layer and a positive electrode material layer, the positive electrode material layer is arranged on at least one surface of the positive electrode collector layer, and the positive electrode material layer includes a positive electrode active material, a positive electrode binder, a positive electrode conductor and a positive electrode thickener.

[0037] Optionally, the positive electrode current collector layer is selected from aluminum foil.

[0038] Optionally, the positive electrode binder includes at least one of polyvinylidene fluoride (PVDF), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinylether, polymethyl methacrylate (PMMA), polyhexafluoropropylene or styrene butadiene rubber (SBR). In the positive electrode material layer, the mass fraction of the positive electrode binder ranges from 2% to 4%.

[0039] Optionally, the negative electrode plate 213 includes a stacked negative electrode current collector layer and a negative electrode material layer, the negative electrode material layer is arranged on at least one surface of the negative electrode current collector layer, and the negative electrode material layer includes a negative electrode active material, a negative electrode binder, a negative electrode conductive agent and a negative electrode thickener.

[0040] Optionally, the negative electrode current collector layer is selected from copper foil.

[0041] Optionally, the negative electrode binder includes at least one of polyvinylidene fluoride (PVDF), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinylether, polymethyl methacrylate (PMMA), polyhexafluoropropylene or styrene butadiene rubber (SBR). In the negative electrode material layer, the mass fraction of the negative electrode binder ranges from 2% to 4%.

[0042] The present application provides an electrolyte 100, which includes: a first additive and a second additive, wherein the first additive is a thioether additive, and the end group of the first additive includes a reactive group; and the second additive is a cyclic sulfonate additive.

[0043] It is to be understood that, in the present application, "reactive group" refers to a part of a molecule that has activity and reactivity.

[0044] It can be understood that the first additive includes a thioether bond, and in the electrolyte 100, the number of the reactive groups is plural, and the number of the thioether bonds is plural.

[0045] It can be understood that in the electrolyte 100, the first additive and the second additive are both film-forming additives.

[0046] In this embodiment, the electrolyte 100 includes a first additive, which is a thioether additive and the terminal group is a reactive group. In other words, the first additive includes a thioether bond, and the multiple reactive groups react with each other to generate a polythioether derivative with a higher degree of polymerization. The sulfur in the polythioether derivative contains lone pairs of electrons, which are easier to coordinate and deintercalate with lithium ions, so that the polythioether derivative has a stronger interaction with lithium ions, which is beneficial to reduce the impedance of lithium ion transmission in the electrolyte 100. Furthermore, the polythioether derivative has a low solubility in the electrolyte 100 and can be preferentially adsorbed on the damaged surface of the negative electrode plate 213 to further reduce the interface impedance of lithium ions entering from the electrolyte 100 to the negative electrode plate 213, reduce the charge transfer impedance, and promote the desolvation process of lithium ions at the interface between the electrolyte 100 and the negative electrode plate 213. Furthermore, the first additive is easy to form a polysulfide derivative with a high degree of polymerization, and the SEI (Solid Electrolyte Interface) film with the polysulfide derivative has good flexibility on the surface of the negative electrode plate 213, which is conducive to accelerating the transmission speed of lithium ions and ultimately improving the cycle capacity retention rate of the battery 200. In addition, the electrolyte 100 also includes a second additive, which is a cyclic sulfonate additive. The second additive breaks the SO bond in the electrolyte 100, and the second additive opens the ring and generates a flexible SEI film containing polysulfonate at the interface between the negative electrode plate 213 and the electrolyte 100. The SEI film has good chemical stability, thereby improving the stability of the electrolyte 100 at high temperatures. The polysulfonate formed by the second additive will further decompose into inorganic components such as lithium sulfonate and lithium sulfide, so that the inorganic components in the SEI film increase, further improving the thermal stability of the SEI film.When the electrolyte 100 includes the first additive and the second additive at the same time, the first additive and the second additive have a synergistic effect. On the one hand, the polysulfide derivative generated by the first additive is adsorbed on the surface of the negative electrode plate 213, and the polysulfide derivative has a strong interaction with lithium ions, which is beneficial to increase the concentration of lithium ions on the interface between the negative electrode plate 213 and the electrolyte 100. The greater the concentration of lithium ions, the higher the concentration of reactants in the decomposition reaction of the polysulfonate generated by the second additive, which is beneficial to promote the decomposition of the polysulfonate. The decomposition reaction equilibrium of the acid ester shifts to the right, promoting the decomposition of the polysulfonic acid ester and forming lithium sulfonate, lithium sulfide, etc. The SEI film includes organic substances such as polysulfide derivatives and polysulfonic acid esters, and includes inorganic substances such as lithium sulfide and lithium sulfonic acid esters. Polysulfide derivatives, polysulfonic acid esters, lithium sulfide, and lithium sulfonic acid esters all contain sulfur, and there is an intermolecular synergistic effect, which improves the stability of the SEI film at high temperatures without reducing the conductivity of the SEI film, so that the electrolyte 100 has good stability at both room temperature and high temperature, and is also convenient for the electrolyte 100 to be stored in a high temperature environment. On the second aspect, the SEI film containing polysulfonic acid ester formed by the second additive has a low ionic conductivity at the interface of the negative electrode plate 213, which may cause the battery 200 to increase rapidly in the initial impedance when the electrolyte 100 is applied to the battery 200, thereby reducing the room temperature performance of the battery 200. Correspondingly, the polysulfide derivative formed by the first additive has excellent ion conductivity, and the first additive can neutralize the deficiencies of the second additive in ion conductivity, so that the electrolyte 100 also has good ion conductivity at room temperature. On the third aspect, the first additive can make the final SEI film have an inorganic component of lithium sulfide, which is beneficial to improve the thermal stability of the SEI film, thereby improving the thermal stability of the electrolyte 100. In summary, the electrolyte 100 of this embodiment has good thermal stability and high ionic conductivity. When the electrolyte 100 is applied to the battery 200, the battery 200 has good cycle performance and high safety performance, and has good high temperature storage performance.

[0047] In some embodiments, the first additive has the structural formula: Among them, R1 is selected from at least one of vinyl, ethynyl and propylene oxide; R2 is selected from at least one of vinyl, ethynyl and propylene oxide.

[0048] It can be understood that in the electrolyte 100, the number of R1 is plural, and the number of R2 is plural.

[0049] In this embodiment, vinyl and ethynyl are functional groups with unsaturated bonds. When R1 and R2 are selected from at least one of vinyl and ethynyl, vinyl and ethynyl are easy to obtain electrons, and multiple terminal groups R1 react with multiple terminal groups R2 to promote multiple structural formulas. Similarly, when R1 and R2 are selected from propylene oxide, propylene oxide is easy to open the ring, and propylene oxide has a reactive property, and can open the ring to form multiple structural formulas. A polymerization reaction occurs to form a polysulfide derivative. The sulfur in the polysulfide derivative contains lone pairs of electrons, which are easier to coordinate and deintercalate with lithium ions, so that the polysulfide derivative has a stronger interaction with lithium ions, thereby helping to reduce the impedance of lithium ion transmission in the electrolyte 100. Optionally, in some embodiments, a plurality of structural formulas such as The polysulfide derivatives formed by the monomer structure have a spiral chain structure, which is conducive to forming a lithium ion transmission channel and facilitating the improvement of the lithium ion transmission efficiency. In addition, since vinyl, ethynyl and propylene oxide have high reactivity, the polysulfide derivatives formed by the first additive have a high degree of polymerization, so that the SEI film containing the polysulfide derivatives has good flexibility, which is conducive to improving the lithium ion transmission efficiency. Furthermore, as the degree of polymerization of the polysulfide derivatives increases, the solubility of the polysulfide derivatives in the electrolyte 100 is lower, and they can be preferentially adsorbed on the damaged surface of the negative electrode plate 213, so as to further reduce the interface impedance of lithium ions entering from the electrolyte 100 to the negative electrode plate 213, reduce the charge transfer impedance, and promote the desolvation process of lithium ions at the interface between the electrolyte 100 and the negative electrode plate 213.

[0050] In some embodiments, the first additive is selected from and At least one of .

[0051] It is understandable that when the first additive is selected from When R1 and R2 are both selected from vinyl, when the first additive is selected from When R1 and R2 are selected from ethynyl, when the first additive is selected from When R1 and R2 are selected from propylene oxide.

[0052] In this embodiment, when the electrolyte 100 is applied to the battery 200, and the first additive is selected from and When at least one of the first additives is present, the monomer structures of the multiple first additives are prone to polymerization reaction to form polysulfide derivatives with a high degree of polymerization, so as to adhere to the surface of the negative electrode plate 213, reduce the impedance of lithium ion transmission between the interface of the electrolyte 100 and the negative electrode plate 213, and the electrolyte 100 has good ion conductivity. The first additive can also neutralize the deficiency of the second additive in ion transmission performance, and adsorb lithium ions to increase the concentration of lithium ions on the surface of the negative electrode plate 213, thereby promoting the ring-opening polymerization and decomposition of the second additive, so that the SEI film formed on the surface of the negative electrode plate 213 has more inorganic components, and improves the thermal stability of the SEI film, so that the electrolyte 100 has both high ion conductivity and good thermal stability. When the electrolyte 100 is applied to the battery 200, the battery 200 has good cycle performance and safety performance.

[0053] It can be understood that in the structural formula of the first additive, R1 and R2 can select different groups. This embodiment only shows an example in which R1 and R2 select the same group, which should not be understood as a limitation on the groups that can be selected by R1 and R2.

[0054] In some embodiments, in the electrolyte 100 , the mass fraction a of the first additive is in the range of 0.1%≤a≤2%.

[0055] It can be understood that, in the electrolyte 100 , the mass fraction a of the first additive is the ratio of the mass of the first additive to the mass of the electrolyte 100 .

[0056] Specifically, the mass fraction a of the first additive may be, but is not limited to, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.8%, 1.9% and 2%, etc.

[0057] In the electrolyte 100 provided in the present embodiment, when the mass fraction a of the first additive satisfies the range of 0.1%≤a≤2%, the mass fraction of the first additive is within a reasonable range, and the degree of polymerization of the polysulfide derivative formed by the polymerization of the first additive is within a reasonable range. On the one hand, the SEI film containing the polysulfide derivative formed by the first additive is not easily dissolved by the electrolyte 100, and can be attached to the surface of the negative electrode plate 213, and the sulfur in the polysulfide derivative has a strong interaction with lithium ions, which increases the concentration of lithium ions at the interface of the negative electrode plate 213 while reducing the charge transfer impedance, thereby facilitating the ring opening of the second additive and forming a polysulfonate with a higher polymer, and further promoting the decomposition of the polysulfonate to generate lithium sulfonate, lithium sulfide, etc., so as to increase the content of inorganic components in the SEI film and improve the thermal stability of the SEI film, so that the electrolyte 100 has both good transmission performance for lithium ions and good thermal stability. On the other hand, the SEI film containing the polysulfide derivative is not too thick to increase the internal resistance of the battery 200, so that the battery 200 has a smaller internal resistance, better cycle performance and safety performance. When the mass fraction of the first additive is too large, the polymerization degree of the polysulfide derivative formed by the polymerization of the first additive is too high, and the SEI film formed by the first additive on the surface of the negative electrode plate 213 is too thick, which will increase the charge transfer impedance, and lithium precipitation may occur at the interface of the negative electrode plate 213, resulting in the loss of active lithium ions in the battery 200. When the electrolyte 100 is applied to the battery 200, the internal resistance of the battery 200 will be increased, and the cycle performance of the battery 200 will be reduced. When the mass fraction of the first additive is too small, the polymerization degree of the polysulfide derivative formed by the polymerization of the first additive is too low. On the one hand, the lower the degree of polymerization of the polysulfide additive, the higher its solubility in the electrolyte 100. In other words, the polysulfide derivatives with a low degree of polymerization are easily dissolved by the electrolyte 100, so that the polysulfide derivatives cannot be preferentially adsorbed on the surface of the negative electrode plate 213, and then it is difficult to increase the concentration of lithium ions on the surface of the negative electrode plate 213, so that the first additive is difficult to play a role in promoting the ring-opening polymerization of the second additive. The degree of polymerization of the polysulfonate formed by the second additive is relatively low, and the inorganic substances such as lithium sulfonate formed after its decomposition are relatively small, so that the thermal stability of SEI is poor, that is, the thermal stability of the electrolyte 100 is poor. On the other hand, the polysulfide derivatives with a low degree of polymerization contain less sulfur, which weakens the interaction of the polysulfide derivatives with lithium ions, thereby reducing the ionic conductivity of the SEI film formed by the first additive and reducing the performance of the electrolyte 100 at room temperature.

[0058] Preferably, in the electrolyte 100, the mass fraction a of the first additive is in the range of 0.2%≤a≤1%. Specifically, the mass fraction a of the first additive may be, but is not limited to, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% and 1%, etc.

[0059] In some embodiments, the structural formula of the second additive is: Wherein, R3 is selected from at least one of methyl, ethyl, propyl, butyl and sulfonate groups.

[0060] In the present embodiment, the structural formula of the second additive is a ring structure, and the second additive contains a sulfonate group. When the electrolyte 100 is applied to the battery 200, the SO bond in the second additive is easily broken and opened, and the second additive generates an SEI film containing polysulfonate with a high degree of polymerization at the interface between the negative electrode plate 213 and the electrolyte 100. The SEI film has good flexibility and good chemical stability, thereby improving the stability of the electrolyte 100 at high temperatures. Furthermore, under the promotion of the first additive, the polysulfonate formed by the second additive will further decompose into inorganic components such as lithium sulfonate and lithium sulfide, so that the inorganic components in the SEI film are increased, and the thermal stability of the SEI film is further improved, thereby improving the thermal stability of the electrolyte 100. Furthermore, in the structural formula of the second additive, R3 is selected from at least one of methyl, ethyl, propyl, butyl and sulfonate groups, which is beneficial to promote multiple structural formulas such as The monomers undergo ring-opening polymerization to form polysulfonates with a high degree of polymerization, so that the lithium sulfonate and lithium sulfide formed by the decomposition of the polysulfonates increase, so that the SEI film has more inorganic components, and ultimately the electrolyte 100 has better stability at high temperatures, thereby improving the performance of the electrolyte 100 and the high-temperature storage performance.

[0061] In some embodiments, the second additive is selected from and At least one of .

[0062] In this embodiment, when the second additive is selected from and When at least one of the above is present, the second additive is a ring structure and contains a sulfonate group. Under the action of the first additive, the second additive is easy to form a SEI film containing polysulfonate with a high degree of polymerization on the surface of the negative electrode plate 213, and further decomposes to form inorganic components such as lithium sulfonate and lithium sulfide, so that the SEI film has better thermal stability, thereby improving the thermal stability of the battery 200 in a high temperature environment, and improving the performance of the electrolyte 100 and the high temperature storage performance.

[0063] In some embodiments, in the electrolyte 100 , the mass fraction b of the second additive is in the range of 0.1%≤b≤3%.

[0064] It can be understood that, in the electrolyte 100 , the mass fraction b of the second additive is the ratio of the mass of the second additive to the mass of the electrolyte 100 .

[0065] Specifically, the mass fraction b of the second additive can be, but is not limited to, 0.1%, 0.3%, 0.4%, 0.6%, 0.7%, 0.9%, 1%, 1.1%, 1.3%, 1.5%, 1.8%, 2%, 2.1%, 2.2%, 2.4%, 2.5%, 2.7%, 2.8%, 2.9% and 3%, etc.

[0066] In the electrolyte 100 provided in this embodiment, when the mass fraction b of the second additive satisfies the range of 0.1%≤b≤3%, the mass fraction of the second additive is within a reasonable range, and the degree of polymerization of the polysulfonate formed by the second additive is within a reasonable range, which can prevent the degree of polymerization of the polysulfonate from being too large and greatly reduce the ion conductivity of the electrolyte 100. On the other hand, under the promotion of the first additive, the polysulfonate decomposes and forms more lithium sulfonate, lithium sulfide, etc., so that the inorganic components in the SEI film increase, and the thermal stability of the SEI film is improved. When the electrolyte 100 is applied to the battery 200, the electrolyte 100 has high ionic conductivity and good thermal stability at both normal temperature and high temperature environments, so that the battery 200 has good cycle performance and safety performance at both normal temperature and high temperature environments. When the mass fraction of the second additive is too large, the SEI film containing polysulfonate formed by the second additive is too thick, and the ion conductivity of the polysulfonate itself is poor, which greatly increases the ion transfer impedance. When the electrolyte 100 is applied to the battery 200, the impedance of the battery 200 increases rapidly in the initial stage, so that the cycle performance of the battery 200 at room temperature is poor. When the mass fraction of the second additive is too small, the polymerization degree of the polysulfonate formed by the polymerization of the second additive is low, which reduces the flexibility of the SEI film formed by the second additive, reduces the chemical stability of the SEI film, and may reduce the stability of the electrolyte 100 at room temperature and high temperature. On the other hand, if the polymerization degree of the polysulfonate is low, the amount of lithium sulfonate, lithium sulfide, etc. formed by the decomposition of the polysulfonate is small, so that the inorganic components of the SEI film formed on the surface of the negative electrode plate 213 are small, and it is difficult to effectively improve the thermal stability of the SEI film, thereby reducing the thermal stability of the electrolyte 100.

[0067] Preferably, the mass fraction b of the second additive is in the range of 0.3%≤b≤1.5%. Specifically, the mass fraction b of the second additive may be, but is not limited to, 0.3%, 0.4%, 0.6%, 0.7%, 0.9%, 1%, 1.1%, 1.3%, 1.5%.

[0068] In some embodiments, in the electrolyte 100 , the mass fraction of the first additive is a, and the mass fraction of the second additive is b, and the relationship is satisfied: 0.1≤a / b≤2.

[0069] Specifically, the value of a / b can be, but is not limited to, 0.1, 0.2, 0.4, 0.5, 0.6, 0.8, 0.9, 1, 1.1, 1.3, 1.4, 1.6, 1.7, 1.8, 1.9 and 2, etc.

[0070] Optionally, in some embodiments, the mass fraction of the first additive is greater than or equal to the mass fraction of the second additive; in other embodiments, the mass fraction of the first additive is less than the mass fraction of the second additive.

[0071] In the electrolyte 100 provided in this embodiment, when the mass fraction a of the first additive and the mass fraction b of the second additive satisfy the relationship 0.1≤a / b≤2, the mass fraction of the first additive and the mass fraction of the second additive are both within a reasonable range. On the one hand, the SEI film containing polysulfide derivatives formed by the first additive is not easily dissolved by the electrolyte 100, and can be attached to the surface of the negative electrode plate 213, and increase the concentration of lithium ions at the interface of the negative electrode plate 213, thereby facilitating the ring opening of the second additive and forming a higher polymer polysulfonate, and further promoting the decomposition of the polysulfonate to generate lithium sulfonate, lithium sulfide, etc., so as to increase the content of inorganic components in the SEI film and improve the thermal stability of the SEI film, so that the electrolyte 100 has both good transmission performance for lithium ions and good thermal stability. On the other hand, the SEI film containing polysulfide derivatives and polysulfonates is not too thick to increase the internal resistance of the battery 200, so that the battery 200 has a smaller internal resistance, better cycle performance and safety performance. When the value of a / b is too large, the mass fraction of the first additive is too large, or the mass fraction of the second additive is too small. When the mass fraction of the first additive is too large, the polymerization degree of the polysulfide derivative formed by the polymerization of the first additive is too high, and the SEI film formed by the first additive on the surface of the negative electrode plate 213 is too thick, which will increase the charge transfer impedance. When the electrolyte 100 is applied to the battery 200, the internal resistance of the battery 200 will be increased, and the cycle performance of the battery 200 will be reduced. When the mass fraction of the second additive is too small, even if the first additive can promote the polymerization and decomposition of the second additive, the polymerization degree of the polysulfonate formed by the second additive on the surface of the negative electrode plate 213 is still small, which reduces the flexibility of the SEI film formed by the second additive, reduces the chemical stability of the SEI film, and may reduce the stability of the electrolyte 100 at room temperature and high temperature environments. On the other hand, if the degree of polymerization of the polysulfonic acid ester is low, the amount of lithium sulfonate, lithium sulfide, etc. formed by the decomposition of the polysulfonic acid ester is small, so that the inorganic components of the SEI film formed on the surface of the negative electrode plate 213 are small, and it is difficult to effectively improve the thermal stability of the SEI film, thereby reducing the thermal stability of the electrolyte 100. When the value of a / b is too small, the mass fraction of the first additive is too small, or the mass fraction of the second additive is too large. When the mass fraction of the first additive is too small, the degree of polymerization of the polysulfide derivative formed by the polymerization of the first additive is too low.On the one hand, polysulfide derivatives with a low degree of polymerization are easily dissolved by the electrolyte 100, so that the polysulfide derivatives cannot be preferentially adsorbed on the surface of the negative electrode plate 213, and then it is difficult to increase the concentration of lithium ions on the surface of the negative electrode plate 213, so that the first additive is difficult to promote the ring-opening polymerization of the second additive. The polymerization degree of the polysulfonate formed by the second additive is relatively low, and the inorganic substances such as lithium sulfonate formed after its decomposition are relatively small, so that the thermal stability of the SEI film is poor, that is, the thermal stability of the electrolyte 100 is poor. On the other hand, polysulfide derivatives with a low degree of polymerization contain less sulfur, which weakens the interaction of polysulfide derivatives with lithium ions, thereby reducing the ionic conductivity of the SEI film formed by the first additive and reducing the performance of the electrolyte 100 at room temperature. When the mass fraction of the second additive is too large, the SEI film containing polysulfonate formed by the second additive is too thick, and the ion conductivity of the polysulfonate itself is poor, which greatly increases the ion transfer impedance. When the electrolyte 100 is applied to the battery 200, the impedance of the battery 200 increases rapidly in the initial stage, so that the cycle performance of the battery 200 at room temperature is poor. Therefore, when the value of a / b is too large or too small, the electrolyte 100 cannot have both high thermal stability and ionic conductivity.

[0072] Preferably, the mass fraction a of the first additive and the mass fraction b of the second additive satisfy the relationship: 0.1≤a / b≤1.

[0073] More preferably, the mass fraction a of the first additive and the mass fraction b of the second additive satisfy the relationship: 0.3≤a / b≤0.6.

[0074] In some embodiments, the mass fraction a of the first additive and the mass fraction b of the second additive satisfy the relationship: 1%≤a+b≤3.5%.

[0075] Specifically, the value of a+b can be but is not limited to 1%, 1.1%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4% and 3.5%, etc.

[0076] In this embodiment, when the mass fraction a of the first additive and the mass fraction b of the second additive satisfy the relationship: 1%≤a+b≤3.5%, in the electrolyte 100, the addition amount of the first additive and the addition amount of the second additive are both within a reasonable range, the first additive and the second additive can play a synergistic role, and the SEI film containing polysulfide derivatives formed by the first additive can be attached to the surface of the negative electrode plate 213, and increase the concentration of lithium ions at the interface of the negative electrode plate 213, thereby facilitating the second additive to open the ring and form a higher polymer polysulfonate, and further promote the decomposition of the polysulfonate to generate lithium sulfonate, lithium sulfide, etc., so as to increase the content of inorganic components in the SEI film and improve the thermal stability of the SEI film, so that the electrolyte 100 has both good transmission performance for lithium ions and good thermal stability. In addition, it can be avoided that the mass fraction of the first additive and / or the mass fraction of the second additive is too large to increase the internal resistance of the battery 200, so that the battery 200 has good cycle stability in both normal temperature environment and high temperature environment. When the value of a+b is too large, the SEI film formed by the first additive and the second additive is too thick, which increases the transfer impedance of lithium ions, thereby reducing the cycle performance of the battery 200. When the value of a+b is too small, the degree of polymerization of the polysulfide derivative formed by the polymerization of the first additive is too low, and the SEI film containing the polysulfide derivative may be partially dissolved by the electrolyte 100, so that the polysulfide derivative cannot be preferentially adsorbed on the surface of the negative electrode plate 213, and then it is difficult to increase the concentration of lithium ions on the surface of the negative electrode plate 213, so that the first additive is difficult to play a role in promoting the ring-opening polymerization of the second additive, and the polymerization degree of the polysulfonate formed by the second additive is low, and the inorganic substances such as lithium sulfonate formed after its decomposition are less, so that the thermal stability of SEI is poor, that is, the thermal stability of the electrolyte 100 is poor.

[0077] Optionally, the electrolyte 100 further includes a solvent, and the solvent is used to dissolve the first additive and the second additive. The solvent includes a cyclic carbonate and a chain carbonate, the cyclic carbonate includes at least one of ethylene carbonate and propylene carbonate, and the chain carbonate includes at least one of dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.

[0078] Optionally, in the electrolyte 100, the mass fraction of the solvent ranges from 60% to 85%. Specifically, the mass fraction of the solvent may be, but is not limited to, 60%, 62%, 65%, 66%, 68%, 70%, 72%, 74%, 76%, 78%, 80%, 82%, 83%, 85%, etc.

[0079] Optionally, in some embodiments, the solvent includes ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate, and the mass ratio of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate is 2:1:2.

[0080] Optionally, the electrolyte 100 also includes an electrolyte lithium salt, which is dissolved in a solvent, and the lithium salt includes one or more of LiPF6, LiBF4, LiFSi, LiTFSi, LiBOB, LiODFP, LiODFB, LiPO2F2 or CF3SO3Li.

[0081] The technical solution of this application is further introduced in the following with multiple embodiments:

[0082] Example 1 to Example 16, Comparative Example 1 to Comparative Example 6:

[0083] 1. Preparation of electrolyte 100:

[0084] In an argon atmosphere glove box with a moisture content of ≤1ppm, ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 2:1:2, and then the dried electrolyte lithium hexafluorophosphate is dissolved in the solvent and stirred until completely dissolved and uniformly dissolved. Fluoroethylene carbonate (FEC), ethylene carbonate (VC), the first additive, and the second additive are added and mixed uniformly to obtain the electrolyte 100 of Examples 1 to 16 and Comparative Examples 1 to 6.

[0085] Wherein, the first additive is a thioether additive, and the terminal group of the first additive includes a reactive group; the second additive is a cyclic sulfonate additive.

[0086] Among them, in the electrolyte 100 of Examples 1 to 16 and Comparative Examples 1 to 6, the type of the first additive and the type of the second additive are as shown in Table 1, and in the electrolyte 100, the value of the mass fraction a of the first additive, the value of the mass fraction b of the second additive, and the value of a / b are as shown in Table 1.

[0087] 2. Preparation of electrode assembly 210:

[0088] (1) Preparation of positive electrode sheet 211: The positive electrode active material lithium iron phosphate, the positive electrode conductive agent conductive carbon black (SP), and the positive electrode binder polyvinylidene fluoride (PVDF) are dispersed in a solvent N-methylpyrrolidone (NMP) according to a mass ratio of 97:0.7:2.3, and different mass percentages of PVDF are added and mixed uniformly to obtain a positive electrode slurry with a solid content of 60wt%; the positive electrode slurry is coated on the aluminum foil of the positive electrode collector layer, and after drying, cold pressing, slitting, and cutting, a positive electrode material layer is formed to obtain a positive electrode sheet 211.

[0089] (2) Preparation of negative electrode sheet 213: artificial graphite as negative electrode active material, conductive carbon black (SP) as negative electrode conductor, carboxymethyl cellulose (CMC) as negative electrode thickener and styrene-butadiene rubber (SBR) as negative electrode binder are dispersed in deionized water at a mass ratio of 96.5:0.5:1:2 and mixed evenly to obtain a negative electrode slurry with a solid content of 50 wt%. The negative electrode slurry is coated on the negative electrode current collector aluminum foil, and after drying, cold pressing, slitting and cutting, a negative electrode material layer is formed to obtain a negative electrode sheet 213.

[0090] (3) Preparation of the diaphragm 212: A 16 μm polyethylene film is used as the diaphragm 212.

[0091] The prepared positive electrode sheet 211, separator 212, and negative electrode sheet 213 are stacked in order so that the separator 212 is located between the positive electrode sheet 211 and the negative electrode sheet 213, and a bare cell is obtained after winding. The electrode tabs are welded on the bare cell to obtain the electrode assembly 210.

[0092] 3. Preparation of battery 200:

[0093] The electrode assembly 210 is assembled into the outer package, and the electrolyte 100 of Examples 1 to 16 and Comparative Examples 1 to 6 is injected. The battery cells are packaged, left to stand, formed, shaped, and capacity tested, etc., to finally prepare Implementation Batteries 1 to Implementation Batteries 16 and Comparative Batteries 1 to Comparative Batteries 6.

[0094] Among them, the electrolyte 100 of Example 1 is applied to the implementation battery 1, the electrolyte 100 of Example 2 is applied to the implementation battery 2, the electrolyte 100 of Comparative Example 1 is applied to the comparison battery 1, the electrolyte 100 of Comparative Example 2 is applied to the comparison battery 2, and so on.

[0095] Table 1 below shows the composition parameters of the electrolyte 100 of Examples 1 to 16 and Comparative Examples 1 to 6.

[0096] Table 1: Composition parameters of the electrolyte 100 of Examples 1 to 16 and Comparative Examples 1 to 6.

[0097]

[0098]

[0099] Among them, in Table 1, the structural formula of formula (I-1) of the first additive is: The structural formula of the first additive (I-2) is: The structural formula of the first additive (I-3) is:

[0100] The structural formula of the second additive (II-1) is: The structural formula of the second additive (II-2) is: The structural formula of the second additive (II-3) is:

[0101] 4. Performance tests of implementation batteries 1 to implementation batteries 16 and comparison batteries 1 to comparison batteries 6:

[0102] (1) Testing of the cycle performance of implementation batteries 1 to implementation batteries 16 and comparative batteries 1 to comparative batteries 6 at room temperature:

[0103] The above-mentioned implementation batteries 1 to implementation batteries 16 and comparison batteries 1 to comparison batteries 6 were subjected to constant current charge and discharge cycle tests on a charge and discharge instrument. The test temperature was 25°C, the charge and discharge rate was 1C (the size of the charge and discharge current is usually expressed by the charge and discharge rate, and the calculation formula of the charge and discharge current is: charge and discharge current = charge and discharge rate × rated capacity of battery 200), and the charge and discharge voltage window was 2.5V to 3.65V (that is, the charge cut-off voltage of battery 200 is 3.65V, and the discharge cut-off voltage of battery 200 is 2.5V; it is generally believed that when the charge cut-off voltage is ≥4V, the charge cut-off voltage of battery 200 is higher), and the capacity retention rate after 500 cycles was calculated. The calculation formula is: capacity retention rate after the Nth cycle = (discharge capacity after the Nth cycle / discharge capacity of the first cycle) × 100%.

[0104] A complete charge and discharge is usually called a charge and discharge cycle, that is, the battery 200 is first charged from 2.5V to 3.65V, and then discharged from 4.2V to 3.65V, thus forming a charge and discharge cycle. Cycle N times means repeating the above process N times.

[0105] Table 2 shows the capacity retention rates of Example Batteries 1 to 16 and Comparative Batteries 1 to 6 after 500 cycles at 25° C.

[0106] (2) Testing of the cycle performance of the implementation batteries 1 to the implementation batteries 16 and the comparative batteries 1 to the comparative batteries 6 at high temperatures:

[0107] The above-mentioned implementation batteries 1 to implementation batteries 16 and comparison batteries 1 to comparison batteries 6 were subjected to constant current charge and discharge cycle tests on a charge and discharge instrument. The test temperature was 45°C, the charge and discharge rate was 1C (the size of the charge and discharge current is usually expressed by the charge and discharge rate, and the calculation formula of the charge and discharge current is: charge and discharge current = charge and discharge rate × rated capacity of battery 200), and the charge and discharge voltage window was 2.5V to 3.65V (that is, the charge cut-off voltage of battery 200 is 3.65V, and the discharge cut-off voltage of battery 200 is 2.5V; it is generally believed that when the charge cut-off voltage is ≥4V, the charge cut-off voltage of battery 200 is higher), and the capacity retention rate after 500 cycles was calculated. The calculation formula is: capacity retention rate after the Nth cycle = (discharge capacity after the Nth cycle / discharge capacity of the first cycle) × 100%.

[0108] A complete charge and discharge is usually called a charge and discharge cycle, that is, the battery 200 is first charged from 2.5V to 3.65V, and then discharged from 4.2V to 3.65V, thus forming a charge and discharge cycle. Cycle N times means repeating the above process N times.

[0109] Table 2 shows the capacity retention rates of Example Batteries 1 to 16 and Comparative Batteries 1 to 6 after 500 cycles at 45° C.

[0110] (3) Testing of storage performance of implementation batteries 1 to implementation batteries 16 and comparative batteries 1 to comparative batteries 6 at high temperatures:

[0111] The implementation batteries 1 to 16 and the comparison batteries 1 to 6 were placed separately in a thermostat in sequence, the temperature of the thermostat was adjusted to 25°C, and the battery was allowed to stand for 10 minutes. The battery 200 was charged with a constant current at a charge and discharge rate of 0.33C until the voltage of the battery 200 was 4.4V, and then the battery 200 was charged with a constant voltage of 4.4V until the voltage of the battery 200 was cut off at 0.05C, and the battery was allowed to stand for 30 minutes, and the initial fully charged volume V0 of the electrode assembly 210 was tested; the temperature of the thermostat was adjusted to 60°C, and the battery was allowed to stand for 30 minutes. The battery 200 was charged with a constant current at a charge and discharge rate of 0.33C until the voltage of the battery 200 was 4.4V, and the battery was allowed to stand for 1 hour. After the above steps were repeated twice, the battery 200 was recharged, and the battery 200 was stored for 60 days. After the electrode assembly 210 was cooled, the fully charged volume V1 of the electrode assembly 210 was tested at this time; the volume expansion rate of the electrode assembly 210 stored at 60°C for 60 days = [(V1 / V0)-1]×100%.

[0112] Table 2 shows the values ​​of the volume expansion ratios of Example Batteries 1 to 16 and Comparative Batteries 1 to 6 when stored at 60° C. for 60 days.

[0113] Table 2 below shows the performance parameters of implementation batteries 1 to implementation batteries 16 and comparison batteries 1 to comparison batteries 6.

[0114] Table 2: Performance parameters of implementation batteries 1 to implementation batteries 16 and comparative batteries 1 to comparative batteries 6.

[0115]

[0116] It can be understood that the capacity retention rate of 500 cycles at 25°C can characterize the cycle performance of the battery 200 under normal temperature environment, and the greater the capacity retention rate of 500 cycles at 25°C, the better the cycle performance of the battery 200 under normal temperature environment; the capacity retention rate of 500 cycles at 45°C can characterize the cycle performance of the battery 200 under high temperature environment, and the greater the capacity retention rate of 500 cycles at 45°C, the better the cycle performance of the battery 200 under high temperature environment; the volume expansion rate after storage at 60°C for 60 days can characterize the high temperature storage performance of the battery 200, and the smaller the volume expansion rate after storage at 60°C for 60 days, the better the high temperature storage performance of the battery 200.

[0117] Please refer to Table 1 and Table 2. From the data of Examples 1 to 16 and Comparative Examples 1 to 6, it can be seen that in the electrolyte 100 of Comparative Example 1, the electrolyte 100 does not include the first additive or the second additive, so that the cycle retention rate of the comparative battery 1 at room temperature and the cycle retention rate at high temperature are both low, and the cycle performance of the comparative battery 1 under room temperature and high temperature environments is poor, and the high-temperature storage performance is poor, and the safety performance of the comparative battery 1 is poor. The electrolyte 100 of Comparative Example 2 includes the first additive but does not include the second additive. Compared with the comparative battery 1, the cycle performance and high-temperature storage performance of the comparative battery 2 are improved, but the high-temperature storage performance of the comparative battery 2 is still poor. This is because the first additive can reduce the charge transfer impedance, and the SEI film formed by the first additive on the surface of the negative electrode plate 213 contains inorganic lithium sulfide, which can improve the thermal stability of the SEI film to a certain extent, thereby improving the thermal stability of the electrolyte 100, and then improving the high-temperature storage performance of the comparative battery 2. However, the addition of the first additive alone has limitations on the improvement of the high-temperature performance of the battery 200. The electrolyte 100 of comparative example 3 includes the second additive but does not include the first additive. Compared with comparative battery 1, the cycle performance and high-temperature storage performance of comparative battery 3 are improved, but the high-temperature storage performance of comparative battery 3 is still poor, which indicates that the second additive contains more inorganic components in the SEI film formed on the surface of the negative electrode plate 213 to improve the thermal stability of the electrolyte 100, but the addition of the second additive alone is also limited to the improvement of the high-temperature performance of the battery 200.The electrolyte 100 of Examples 1 to 16 includes a first additive and a second additive, and the mass fraction a of the first additive satisfies the range of 0.1%≤a≤2%, the mass fraction b of the second additive satisfies the range of 0.1%≤b≤3%, and the value of a / b satisfies the range of 0.1≤a / b≤2, so that the capacity retention rate of the implementation battery 1 to the implementation battery 16 after 500 cycles at 25°C is higher than the capacity retention rate of the comparison battery 1 to the comparison battery 3 after 500 cycles at 25°C, the capacity retention rate of the implementation battery 1 to the implementation battery 16 after 500 cycles at 45°C is higher than the capacity retention rate of the comparison battery 1 to the comparison battery 3 after 500 cycles at 45°C, and the volume expansion rate of the implementation battery 1 to the implementation battery 16 when stored at 60°C for 60 days is less than that of the comparison battery 1 to the comparison battery 3 at 60°C. The volume expansion rate after storage at 60°C for 60 days indicates that: when the electrolyte 100 includes the first additive and the second additive at the same time, the first additive and the second additive have a synergistic effect, and the first additive can not only improve the ion transport performance of the electrolyte 100, but also neutralize the deficiency of the second additive in ion transport performance, and the first additive can promote the second additive to form a polysulfonate with a higher degree of polymerization, so that the polysulfonate decomposes to generate more lithium sulfide and lithium sulfonate, so that the SEI film formed by the first additive and the second additive at the interface of the negative electrode plate 213 has more inorganic components and better thermal stability, so that the corresponding battery 200 has better cycle performance at both room temperature and high temperature, and has better high temperature storage performance. In addition, the mass fraction of the first additive and the mass fraction of the second additive in the electrolyte 100 of Comparative Example 4 are both large, the a / b value in the electrolyte 100 of Comparative Example 5 is too small, and the a / b value in the electrolyte 100 of Comparative Example 6 is too large, which causes the cycle performance of Comparative Battery 4 to Comparative Battery 5 to deviate at room temperature and high temperature, and the high-temperature storage performance to deviate. This shows that: when the a / b value does not meet a reasonable range, the synergistic effect of the first additive and the second additive is weakened. If the mass fraction of the first additive is too small, it is difficult to promote the degradation of the polysulfonate formed by the second additive, thereby reducing the inorganic components of the SEI film, and then causing the cycle performance of the electrolyte 100 to deviate.

[0118] It can be seen from the data of Examples 1 to 4 that, under the same other conditions, as the mass fraction of the first additive gradually increases, the capacity retention of Battery 1 to Battery 4 after 500 cycles at 25°C first increases and then decreases, the capacity retention after 500 cycles at 45°C first increases and then decreases, and the volume expansion after storage at 60°C for 60 days first decreases and then increases. This shows that if the mass fraction of the first additive is too large or too small, the first additive will weaken the thermal stability and high-temperature storage performance of the electrolyte 100. When the mass fraction of the first additive meets the reasonable range, the SEI film containing polysulfide derivatives formed by the first additive is not easily dissolved by the electrolyte 100, and can be attached to the surface of the negative electrode plate 213, and the sulfur in the polysulfide derivative has a strong interaction with lithium ions, which increases the concentration of lithium ions at the interface of the negative electrode plate 213 while reducing the charge transfer impedance, thereby facilitating the ring opening of the second additive and forming a higher polymer polysulfonate, and further promoting the decomposition of the polysulfonate to generate lithium sulfonate, lithium sulfide, etc., so as to increase the content of inorganic components in the SEI film and improve the thermal stability of the SEI film, so that the electrolyte 100 has both good transmission performance and good thermal stability for lithium ions. Preferably, the battery 3 has excellent cycle performance and high temperature storage performance. When the mass fraction of the first additive is too large, the polymerization degree of the polythioether derivative formed by the polymerization of the first additive is too high, and the SEI film formed by the first additive on the surface of the negative electrode plate 213 is too thick, which will increase the charge transfer impedance. When the electrolyte 100 is applied to the battery 200, the internal resistance of the battery 200 will be increased, so that the cycle performance of the implemented battery 4 is relatively low. When the mass fraction of the first additive is too small, the polymerization degree of the polythioether derivative formed by the polymerization of the first additive is relatively low. The polythioether derivative with a low polymerization degree is easily dissolved by the electrolyte 100, so that the polythioether derivative cannot be preferentially adsorbed on the surface of the negative electrode plate 213, and then the first additive is difficult to play the role of promoting the decomposition of the polysulfonic acid ester. The inorganic substances such as lithium sulfonate formed by the polysulfonic acid ester formed by the second additive after decomposition are less, so that the thermal stability of the SEI is poor, that is, the thermal stability of the electrolyte 100 is poor, so that the cycle performance of the implemented battery 1 is relatively low.

[0119] It can be seen from the data of Examples 5 to 8 that, under the same other conditions, as the mass fraction of the second additive gradually increases, the capacity retention of 500 cycles of the battery 5 to 8 at 25°C first increases and then decreases, the capacity retention of 500 cycles at 45°C first increases and then decreases, and the volume expansion of 60 days of storage at 60°C first decreases and then increases, which shows that: if the mass fraction of the second additive is too large or too small, the thermal stability and high-temperature storage performance of the electrolyte 100 will be weakened by the second additive. When the mass fraction of the second additive meets the reasonable range, the degree of polymerization of the polysulfonate formed by the second additive is within a reasonable range, which can prevent the degree of polymerization of the polysulfonate from being too large and greatly reducing the ion conductivity of the electrolyte 100. On the other hand, under the promotion of the first additive, the polysulfonate decomposes and forms more lithium sulfonate, lithium sulfide, etc., so that the inorganic components in the SEI film increase, and the thermal stability of the SEI film is improved. When the electrolyte 100 is applied to the battery 200, the electrolyte 100 has a high ionic conductivity and good thermal stability at both room temperature and high temperature environments, so that the battery 200 has good cycle performance and safety performance at both room temperature and high temperature environments. Preferably, the implementation battery 6 has better cycle performance and high temperature storage performance. When the mass fraction of the second additive is too large, the SEI film containing the polysulfonate formed by the second additive is too thick, and the ion conductivity of the polysulfonate itself is poor, which increases the ion transfer impedance, thereby causing the cycle performance and high temperature storage performance of the implementation battery 8 to deviate. When the mass fraction of the second additive is relatively small, the degree of polymerization of the polysulfonate formed by the polymerization of the second additive is relatively low, and the amount of lithium sulfonate, lithium sulfide, etc. formed by the decomposition of the polysulfonate is relatively small, so that the inorganic components of the SEI film formed on the surface of the negative electrode plate 213 are relatively small, and it is difficult to effectively improve the thermal stability of the SEI film, thereby reducing the thermal stability of the electrolyte 100, and then causing deviations in the cycle performance and high-temperature storage performance of the implemented battery 5.

[0120] From the data of Examples 3, 9 and 10, it can be seen that, under the same other conditions, the structural formula of the first additive in Example 3 is The structural formula of the first additive in Example 9 is The structural formula of the first additive in Example 10 is Implementation battery 3, implementation battery 9 and implementation battery 10 all have a high capacity retention rate and a small volume expansion rate under high temperature environment. This shows that these structural formulas can make the first additive fully play the function of improving the ion conductivity of the electrolyte 100, and can fully promote the decomposition of the second additive to generate more inorganic substances, so that implementation battery 3, implementation battery 9 and implementation battery 10 all have good cycle performance and high temperature storage performance.

[0121] From the data of Examples 3, 11 and 12, it can be seen that, under the same other conditions, the structural formula of the second additive in Example 3 is The structural formula of the second additive in Example 11 is The structural formula of the second additive in Example 12 is Implementation battery 3, implementation battery 11 and implementation battery 12 all have high capacity retention rates and small volume expansion rates in high temperature environments. Among them, implementation battery 3 has the highest capacity retention rate after 500 cycles at 25°C, the highest capacity retention rate after 500 cycles at 45°C, and the lowest volume expansion rate after 60 days of storage at 60°C. This shows that these structural formulas can open the second additive to form polysulfonate, and decompose under the action of the first additive to form inorganic molecules such as lithium sulfonate and lithium sulfide, so that the SEI film has more inorganic components, and further makes the SEI film have better thermal stability. Among them, Containing two sulfonate groups, the polysulfonate formed by the second additive of this structural formula can decompose more inorganic molecules such as lithium sulfonate and lithium sulfide, so that the SEI film has the best thermal stability, and the implemented battery 3 has the best cycle performance and high-temperature storage performance.

[0122] It can be seen from the data of Examples 13 to 16 that when the electrolyte 100 includes the same first additive and second additive, when the sum of the mass fraction of the first additive and the mass fraction of the second additive is constant, by adjusting the value of a / b, it is beneficial to adjust the cycle performance and high temperature storage performance of the battery 200 at high temperature, and more specifically, to adjust the thermal stability of the electrolyte 100. In addition, as the value of a / b increases, the corresponding battery 200 has a cycle performance at room temperature that first increases and then decreases, and a cycle performance at high temperature that first increases and then decreases, and the high-temperature storage performance also first increases and then decreases. This is because: when the mass fraction of the first additive and the mass fraction of the second additive are both within a reasonable range, the SEI film containing polysulfide derivatives formed by the first additive can adhere to the surface of the negative electrode plate 213 and increase the concentration of lithium ions at the interface of the negative electrode plate 213, which is beneficial to promote the second additive to open the ring and form a higher polymer polysulfonate, and further promote the decomposition of the polysulfonate to generate lithium sulfonate, lithium sulfide, etc., so as to increase the content of inorganic components in the SEI film and improve the thermal stability of the SEI film, so that the electrolyte 100 has both good lithium ion transmission performance and good thermal stability. When the value of a / b is too large, the degree of polymerization of the polysulfide derivative formed by the polymerization of the first additive may be too high to increase the charge transfer impedance. In addition, the degree of polymerization of the polysulfonate formed by the second additive on the surface of the negative electrode plate 213 may be too small, and the amount of lithium sulfonate, lithium sulfide, etc. formed by the decomposition of the polysulfonate is small, so that the inorganic components of the SEI film formed on the surface of the negative electrode plate 213 are small, and it is difficult to effectively improve the thermal stability of the SEI film, thereby reducing the thermal stability of the electrolyte 100. When the value of a / b is too small, the degree of polymerization of the polysulfide derivative formed by the polymerization of the first additive may be too low and partially dissolved by the electrolyte 100, so that the polysulfide derivative cannot be preferentially adsorbed on the surface of the negative electrode plate 213, the first additive is difficult to play the role of promoting the ring-opening polymerization of the second additive, the degree of polymerization of the polysulfonate formed by the second additive is too low, and the inorganic substances such as lithium sulfonate salt formed after its decomposition are too small, so that the thermal stability of SEI is biased, that is, the thermal stability of the electrolyte 100 is biased.

[0123] See also Figure 2 and Figure 3 The present application provides an electrical device 300 , which includes: a device body 310 and a battery 200 provided in the present application, and the battery 200 supplies power to the device body 310 .

[0124] It can be understood that the battery 200 is electrically connected to the device body 310 .

[0125] In this embodiment, the electrolyte 100 has not only good ion transmission performance at room temperature and high temperature, but also good thermal stability, so that the battery 200 has good cycle performance and good safety performance at room temperature and high temperature, and the battery 200 has good high temperature storage performance, so the battery 200 can be stored and applied in a high temperature environment to expand the applicable scenarios of the battery 200 and improve the performance of the battery 200. When the battery 200 is applied to the power-consuming device 300, the battery 200 can provide stable power for the device body 310, which is conducive to improving the user experience.

[0126] Optionally, the power-consuming device 300 of the embodiment of the present application may be, but is not limited to, a portable electronic device such as a mobile phone, a tablet computer, a laptop computer, a desktop computer, a smart bracelet, a smart watch, an e-reader, a game console, etc. It may also be a vehicle such as a car, a truck, a car, a truck, a truck, a motor vehicle, a high-speed train, an electric vehicle, etc. In addition, it may also be various household appliances, etc. The present application Figure 2 The electrical equipment 300 of the embodiment is an energy storage battery cabinet.

[0127] It can be understood that the electric device 300 described in this embodiment is merely a form of the electric device 300 used by the battery 200, and should not be understood as a limitation on the electric device 300 provided in this application, nor should it be understood as a limitation on the electric device 300 provided in each embodiment of this application.

[0128] Mentioning "embodiment" and "implementation method" in this application means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of the phrases in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this application can be combined with other embodiments. In addition, it should also be understood that the features, structures or characteristics described in the various embodiments of the present application can be arbitrarily combined to form another embodiment that does not deviate from the spirit and scope of the technical solution of the present application, provided that there is no contradiction between them.

[0129] Finally, it should be noted that the above implementation modes are only used to illustrate the technical solution of the present application and are not intended to limit it. Although the present application has been described in detail with reference to the above preferred implementation modes, a person of ordinary skill in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present application.

Claims

1. An electrolyte, characterized in that: The electrolyte includes: a first additive and a second additive, wherein the first additive is a thioether additive, and the end group of the first additive includes a reactive group; and the second additive is a cyclic sulfonate additive.

2. The electrolyte according to claim 1, characterized in that The structural formula of the first additive is: Among them, R1 is selected from at least one of vinyl, ethynyl and propylene oxide; R2 is selected from at least one of vinyl, ethynyl and propylene oxide.

3. The electrolyte according to claim 1, characterized in that The first additive is selected from and At least one of .

4. The electrolyte according to any one of claims 1 to 3, characterized in that In the electrolyte, the mass fraction a of the first additive is in the range of 0.1%≤a≤2%.

5. The electrolyte according to claim 1, characterized in that The structural formula of the second additive is: Wherein, R3 is selected from at least one of methyl, ethyl, propyl, butyl and sulfonate groups.

6. The electrolyte according to claim 1, characterized in that The second additive is selected from and At least one of .

7. The electrolyte according to claim 5 or 6, characterized in that In the electrolyte, the mass fraction b of the second additive is in the range of 0.1%≤b≤3%.

8. The electrolyte according to claim 1, characterized in that In the electrolyte, the mass fraction of the first additive is a, and the mass fraction of the second additive is b, and the relationship is satisfied: 0.1≤a / b≤2.

9. A battery, characterized in that: The battery comprises: An electrode assembly, the electrode assembly comprising a positive electrode sheet, a separator and a negative electrode sheet; and The electrolyte according to any one of claims 1 to 8, wherein the electrolyte is used to wet at least a portion of the electrode assembly.

10. An electrical device, characterized in that: The electrical equipment includes: The device itself; and The battery of claim 9, wherein the battery is used to power the device body.